A note on cue rates for common minke, fin and humpback whales off West Greenland - Heide-Jørgensen, Mads Peter; Simon , Malene (J. Cetacean Res. Manage., 2023)
Field observations of cue rates for common minke whales, fin whales and humpback whales were conducted in July 1996 and MaySeptember 2006. The cue for minke whales was usually the dorsal ridge breaking the water surface. A total of 295min of surfacings of five minke whales ranging 27-106min were observed and the simple mean was 46.1 surfacings per hour (CV=0.11). The cue for fin and humpback whale surfacings was sometimes the head breaking the surface but most often a blow. Twenty-three trials of fin whale groups ranging 1-4 individuals provided 620min of observations. The simple mean of all the trials was 52 blows hr–1 (CV=0.06). When trials <10min were excluded the surfacing rate remained unchanged, but when trials <30min were excluded the surfacing decreased to 50 blows hr–1 (CV=0.07, n=8 trials). A total of 860min (n=39 trials) and 1,232 blows from surfacing humpback whales were collected from groups of 1-4 individuals. The simple mean of all trials was 71 blows hr–1 (CV=0.07). The minke, fin and humpback whale cue rate estimates are close to values obtained from other studies, but they are the first that are specific to West Greenland and it is suggested that they should be used for correcting abundance estimates obtained from the aerial cue counting method.